2020
DOI: 10.9758/cpn.2020.18.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Dextromethorphan Protect the Valproic Acid Induced Downregulation of Neutrophils in Patients with Bipolar Disorder

Abstract: Objective: Valproic acid (VPA) is an anticonvulsant and commonly long term used as a mood stabilizer for patients with mood disorders. However its chronic effects on the hematological changes were noticed and need to be further evaluated. In this study, we evaluated, in Taiwanese Han Chinese patients with bipolar disorders (BD), the chronic effects of VPA or VPA plus dextromethorphan (DM) on the hematological molecules (white blood cell [WBCs], red blood cells [RBCs], hemoglobin, hematocrit, and platelets). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, low dose of DXM has been reported to help maintain hematologic molecules in patients with bipolar disorder. 20 Hyperdosing with DXM causes intoxicating, hallucinogenic, and dissociative effects. It has been reported that five teenagers who purposefully ingested large doses of DXM obtained over the internet for recreational purposes died as a result of the direct toxic effects of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, low dose of DXM has been reported to help maintain hematologic molecules in patients with bipolar disorder. 20 Hyperdosing with DXM causes intoxicating, hallucinogenic, and dissociative effects. It has been reported that five teenagers who purposefully ingested large doses of DXM obtained over the internet for recreational purposes died as a result of the direct toxic effects of the drug.…”
Section: Discussionmentioning
confidence: 99%